Database on the structure of small ribosomal subunit RNA. - Van de Peer, Y (1996)
The Antwerp database on small ribosomal subunit RNA offers over 4300 nucleotide sequences (August 1995). All these sequences are stored in the form of an alignment based on the adopted secondary structure model, which in turn is corroborated by the observation of compensating substitutions in the alignment. Besides the primary and secondary structure information, literature references, accession numbers and detailed taxonomic information are also compiled. The complete database is made available to the scientific community through anonymous ftp and World Wide Web(WWW).